2018
DOI: 10.1113/jp275902
|View full text |Cite|
|
Sign up to set email alerts
|

Altered synaptic and firing properties of cerebellar Purkinje cells in a mouse model of ARSACS

Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset neurodegenerative disease that includes a pronounced and progressive cerebellar dysfunction. ARSACS is caused by an autosomal recessive loss-of-function mutation in the Sacs gene that encodes the protein sacsin. To better understand the cerebellar pathophysiology in ARSACS, we studied synaptic and firing properties of Purkinje cells from a mouse model of ARSACS, Sacs mice. We found that excitatory synaptic drive was reduced on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 51 publications
(92 reference statements)
8
45
0
Order By: Relevance
“…Interestingly, Purkinje cell damage in the brain of the HbSS-BERK mice has been previously observed (6). Purkinje cells are the principal output neurons of the cerebellar cortical microcircuit, and thus play a fundamental role in coordinating cerebellar function by integrating massive excitatory synaptic input, as well as firing high-frequency and highly regular action potentials in the absence of synaptic drive (8). Purkinje cell malfunction has been observed in mouse models of several forms of ataxia, which exhibit alterations in gait (9,10).…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, Purkinje cell damage in the brain of the HbSS-BERK mice has been previously observed (6). Purkinje cells are the principal output neurons of the cerebellar cortical microcircuit, and thus play a fundamental role in coordinating cerebellar function by integrating massive excitatory synaptic input, as well as firing high-frequency and highly regular action potentials in the absence of synaptic drive (8). Purkinje cell malfunction has been observed in mouse models of several forms of ataxia, which exhibit alterations in gait (9,10).…”
Section: Introductionmentioning
confidence: 96%
“…The exact role of this large, 520-kDa cytoplasmic protein remains unknown, though it has been proposed to have roles in mitochondrial function ( 21 ), protein chaperoning ( 22 ), and the ubiquitin-proteasome system ( 23 ). Further studies have shown that Sacsin knockout results in increased reactive oxygen species production ( 24 ) and alterations in synaptic input and intrinsic firing in cerebellar Purkinje cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCs from the Sacs À/À mouse model have axonal swellings, characteristic of axonal degeneration. Recent studies have revealed abnormal synaptic input and intrinsic firing in cerebellar PCs, as well as in their synaptic output in the deep cerebellar nuclei in a mouse model of ARSACS [29]. These changes in firing have been observed in anterior lobules that later exhibit PCs death showing that synaptic and intrinsic alterations are related to PCs and likely to contribute to disease manifestation in ARSACS.…”
Section: Disease Modelling Of Arsacsmentioning
confidence: 97%